The Role of the Library in Fostering Students’ Reading Habit: A Case in an Islamic Primary School - Ikhsan, Khabibul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Reading interest and reading skills are inextricably linked, fostering a reciprocal relationship that enhances overall literacy and comprehension. Cultivating a strong reading foundation from an early age is crucial, as it lays the groundwork for academic achievement, professional advancement, and personal fulfillment. This study delved into the realm of reading interest and library activities at MI Salafiyah Duwet Pekalongan City, seeking to unravel the intricate connections between these factors and their impact on student learning. The findings revealed that reading interest plays a pivotal role in enabling students to attain their educational objectives and refine their reading proficiency. Furthermore, the study underscored the library's transformative influence on fostering a passion for reading. Students who actively engage with library resources expand their knowledge base, cultivate a deeper appreciation for the written word, and develop a lifelong love of reading. Effective library management encompasses a three-pronged approach: organizing, mobilizing, and building. Organizing involves meticulously crafting a comprehensive library plan that encompasses the collection, staffing, and physical space. Mobilizing entails actively promoting the library's resources and services to the student body and the wider community. Building centers on maintaining the library's infrastructure, ensuring its continued functionality, and implementing necessary improvements to optimize its effectiveness.